Modulation of Adipocyte Size and Fat Pad Weight via Resveratrol Releasing Scaffolds Implanted into the Epididymal Adipose Tissue - Murphy, Kendall P. (J Biomed Mater Res A, 2020)
Lipid overload of the adipose tissue, which can be caused by overnutrition, underlies metabolic disease. We hypothesized that increasing the energy demand of adipose tissue is a promising strategy to combat excessive lipid accumulation. Resveratrol, a natural polyphenol, activates lipid catabolism in fat tissue; however, its clinical success is hindered by poor bioavailability. Here, we implanted resveratrol releasing poly(lactide-co-glycolide) scaffolds into epididymal fat to overcome its poor bioavailability with the goal of enhancing local lipid catabolism. In lean mice, resveratrol scaffolds decreased adipocyte size relative to scaffolds with no drug, a response that correlated with AMP kinase activation. Immunohistochemistry indicated that macrophages and multinucleated giant cells within the scaffold expressed carnitine palmitoyltransferase 1 (CPT1) at higher levels than other cells in the adipose tissue. Furthermore, resveratrol increased CPT1 levels in cultured macrophages. Taken together, we propose that resveratrol scaffolds decrease adipocyte size because resveratrol increases lipid utilization in scaffold-infiltrating immune cells, possibly through elevating CPT1 levels or activity. In a follow-up study, mice that received resveratrol scaffolds 28-days prior to a high fat diet exhibited decreased weight gain, adipose tissue expansion, and adipocyte hypertrophy compared to mice with control scaffolds. Notably, this scaffold-based strategy required a single resveratrol administration compared to the daily regiment generally needed for oral administration. These results indicate that localized delivery of metabolism modulating agents to the adipose tissue may overcome issues with bioavailability and that the role of biomaterials should be further investigated in this therapeutic strategy for metabolic disease.